2014
DOI: 10.1021/es5001566
|View full text |Cite
|
Sign up to set email alerts
|

Emissions from an International Airport Increase Particle Number Concentrations 4-fold at 10 km Downwind

Abstract: We measured the spatial pattern of particle number (PN) concentrations downwind from the Los Angeles International Airport (LAX) with an instrumented vehicle that enabled us to cover larger areas than allowed by traditional stationary measurements. LAX emissions adversely impacted air quality much farther than reported in previous airport studies. We measured at least a 2-fold increase in PN concentrations over unimpacted baseline PN concentrations during most hours of the day in an area of about 60 km2 that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
144
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(160 citation statements)
references
References 15 publications
10
144
2
4
Order By: Relevance
“…Therefore, a passing car could distort the result heavily as they are less interested in the local emissions of that car. Hudda et al (2014) and Choi et al (2012) used a rolling percentile to obtain a baseline concentration to discard the local peaks, as they wanted to map the larger scale variations due to the impact of an airport and a highway, respectively. However, in an urban environment with busy traffic, peak concentrations are an integral part of the air quality that people are typically exposed to.…”
Section: Influence Of Events On Spatial Concentration Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a passing car could distort the result heavily as they are less interested in the local emissions of that car. Hudda et al (2014) and Choi et al (2012) used a rolling percentile to obtain a baseline concentration to discard the local peaks, as they wanted to map the larger scale variations due to the impact of an airport and a highway, respectively. However, in an urban environment with busy traffic, peak concentrations are an integral part of the air quality that people are typically exposed to.…”
Section: Influence Of Events On Spatial Concentration Patternsmentioning
confidence: 99%
“…Mobile measurements are performed with different platforms, e.g. pedestrians (Zwack et al, 2011a), bicycles (Berghmans et al, 2009;Boogaard et al, 2009;Peters et al, 2013;Sullivan and Pryor, 2014), trams (Hagemann et al, 2014;Hasenfratz et al, 2014) and cars (Westerdahl et al, 2005;Hu et al, 2012;Hudda et al, 2014). Mobile measurements are used for a range of different purposes, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsu et al (2014) observed that departures and arrivals on a major runway of Green International Airport (Warwick, RI, USA) had a significant influence on UFP concentrations in a neighbourhood proximate to the end of the runway. In a study carried out at Los Angeles International Airport (CA, USA), Hudda et al (2014) concluded that emissions from the airport increase PNC by 4-to 5-fold at 8-10 km downwind of the airfield, while Shirmohammadi et al (2017) reported that the daily contributions of the airport to PNC were approximately 11 times greater than those from three surrounding freeways. reported that average PNC were 2-and 1.33-fold higher at sites 4 and 7.3 km from Boston (MA, USA) airport when winds were from the direction of the airfield compared to other directions.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline PNCs for each run were derived by taking a 30 s rolling average of the lowest 5 th percentile value of the 1s concentration time series (Hudda et al, 2014). This methodology was adopted to smooth the data and to exclude the impact of micro-scale.…”
Section: Data Acquisitionmentioning
confidence: 99%